2009
DOI: 10.1159/000272030
|View full text |Cite
|
Sign up to set email alerts
|

Management of Cerebrospinal Fluid Leak following Retrosigmoid Posterior Cranial Fossa Surgery

Abstract: Objective: To detail our experience in the management of cerebrospinal fluid (CSF) leak following posterior cranial fossa surgery by the retrosigmoid approach. Patients and Methods: 412 patients who underwent posterior cranial fossa surgery by the retrosigmoid approach for a variety of diseases were included in the study. Results: There were 32 CSF leaks (7.7%) in the 412 patients. Of these, 16 were leaks from the incision site (50%) and 16 (50%) were CSF rhinorrheas. The CSF leaks were documented in 22 of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 20 publications
(14 reference statements)
1
35
0
5
Order By: Relevance
“…The incidence has been reported to range from 1-12.5% after MVD for trigeminal neuralgia 11,19. However, there was no case of CSF leakage after MVD in our series, which is similar to the findings of Bayazit et al6 where there was no CSF leakage after MVD.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The incidence has been reported to range from 1-12.5% after MVD for trigeminal neuralgia 11,19. However, there was no case of CSF leakage after MVD in our series, which is similar to the findings of Bayazit et al6 where there was no CSF leakage after MVD.…”
Section: Discussionsupporting
confidence: 92%
“…Bayazit et al6 in their study found that ten out of the thirty two patients that had CSF leakage after retrosigmoid posterior cranial fossa surgery could be managed conservatively. Twelve patients needed CSF lumbar drainage.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…However, in our patients, CFS leak was the most common problem that was encountered in 2 of 5 patients (40%). In retrosigmoid approach the treatment algorithm of CSF leaks has been established well [9,10] . It includes one or more of the following: conservative treatment with compressive dressing, placement of a lumbar drainage, surgical reexploration and ventriculoatrial or ventriculoperitoneal shunts.…”
Section: Discussionmentioning
confidence: 99%
“…When they occur, treatment is needed to avoid meningitis and rarely death. In adults, CSF leakage after RSS has an average incidence of 10.6% (8) with a range from 0.29 (9) to 68.7% (10). In vestibular schwannoma surgery, the incidence is higher, from 2 to 14%, compared with vestibular nerve section and microvascular decompression procedures which present an average incidence of 6.15% (11).…”
Section: Objectivementioning
confidence: 99%